RHETORICAL MOVES AND LINGUISTIC REALIZATIONS OF RESEARCH ARTICLE ABSTRACTS BY INDONESIAN AUTHORS IN APPLIED LINGUISTICS PUBLISHED IN INTERNATIONAL JOURNALS - Husnul Hakim; Safnil Arsyad; Syahrial Syahrial (Universitas Bengkulu, 2021)
The existence of abstract is compulsory within a research article (RA). Abstract is a summary or brief overview that describes entire content of RA. At a glimpse, abstract tells readers what the RA is all about and at the same time, it acknowledges readers and allows them indirectly to give pre-assessment about quality of the RA. This study aims to find rhetorical moves and linguistic features; tenses and voice forms of RA abstracts by Indonesian authors in Applied Linguistics published in international journals. Using content analysis method, sixty RA abstracts were extracted from two international journals; Indonesian Journal of Applied Linguistics (IJAL) and TEFLIN journal, and examined based on their rhetorical move following five-move model by Hyland (2005) and Arsyad (2014) for fact-finding. The results reveal; 1) Move 2 (Aim/ Purpose), Move 3 (Method) and Move 4 (Finding/ Result) exist in total sixty RA abstracts, unlike Move 1 (Introduction) and Move 5 (Conclusion and Suggestion), 2) The Simple Present Tense is major tense to apply in all rhetorical moves except in Move 3 (Method) in which Past Tense is mostly used. 3) Active voice dominates rhetorical moves except in Move 3 (Method) in which Passive voice is precisely more applied. This study concludes that the use of rhetorical move models and linguistic features in RA abstracts implies the quality of RA abstracts. Indonesian authors are suggested to follow international standards and trends to achieve outstanding RA abstract.